Strengthening the Supervision Authority of Election Socialization through Collaboration Between KPU, Bawaslu, and Regional Governments - Setiawan, Derry; Sejati, Hono; Zaini, Naya Amin (Cognitionis Civitatis et Politicae, 2024)
The background of this study focuses on the challenges faced by the Election Supervisory Body (Bawaslu) in supervising election socialization, including limitations in human resources, insufficient funding, and inadequate infrastructure. Effective supervision of election socialization is crucial for ensuring voter awareness, understanding their rights and responsibilities, and fostering public participation in the electoral process. The aim of this study is to strengthen Bawaslu's supervisory authority through a collaborative approach involving the General Election Commission (KPU) and regional governments. Collaboration among these institutions is expected to address challenges and enhance the effectiveness of election socialization efforts. This study employs a qualitative research method to analyze existing collaborative practices and identify strategies for improving Bawaslu's authority and performance in supervising election socialization in Indonesia. The results indicate that collaborative efforts can create better synergy between Bawaslu, KPU, and regional governments, leading to improved supervision quality and increased public engagement in the electoral process. In conclusion, collaboration is a key strategy for addressing resource limitations and ensuring effective election socialization supervision. Strengthening Bawaslu's authority requires continuous support and engagement from all stakeholders.